ANALYSIS OF PEER INTERACTION ON SPEAKING SKILLS IN CLASS 10 MAN 2 BUKITTINGGI - Neci Oparianti; Reflinda; Veni Roza; Melyann Melani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Speaking is one of the most essential skills in learning a foreign language, yet it often becomes the most challenging for students to master. Many learners struggle with confidence, vocabulary limitations, and anxiety when speaking English. This study explores the role of peer interaction in improving students' speaking skills in Class 10 at MAN 2 Bukittinggi. The research was motivated by preliminary findings that showed varied student preferences some felt more comfortable interacting with peers, while others preferred teacher-led activities. Using a qualitative approach, the researcher collected data through classroom observations and semi-structured interviews with one English teacher and six students from Class 10 E.2. The findings revealed that peer interaction significantly supports the development of speaking skills by creating a more relaxed and supportive learning environment. Students were observed actively participating in discussions, giving feedback, correcting one another, and engaging in various types of peer interaction such as collaboration, tutoring, and modeling. While some students remained dependent on teacher presence, the majority benefited from the freedom and encouragement peer learning provided. Interviews confirmed that students felt more confident and motivated when speaking with friends rather than the teacher. The study concludes that peer interaction is an effective strategy in enhancing speaking skills. It not only improves students’ fluency but also builds their confidence, independence, and social support in the learning process. This approach, when properly designed, can serve as a meaningful component of communicative language teaching.